Deciphering the YY1/ lncRNA BLACAT1/miR-605-3p axis in glioblastoma: implications for therapy - Liang Han; Han Wang; Hong Xie; Xiuming Yu; Haixia Zhou; Zhigang Guo (npj Precision Oncology)
Abstract Glioblastoma multiforme (GBM), an aggressive brain cancer, requires novel therapeutic targets. This study investigates the YY1/lncRNA BLACAT1/miR-605-3p regulatory network in GBM pathogenesis. Using bioinformatics tools and TCGA-GBM datasets, we identified six miR-605-3p target genes (ARPC1B, FOSL1, H6PD, ITGA3, LMAN1, and PXN) strongly correlated with YY1 (p < 0.01). In GBM cells, YY1 mRNA increased ~3.8-fold (p < 0.01), BLACAT1 ~ 2.4–2.7-fold (p < 0.01), and target genes ~1.8–2.5-fold (p < 0.05), while miR-605-3p decreased to ~0.3-fold (p < 0.01). YY1 knockout reduced BLACAT1 to 0.33 (p < 0.001), reversed by miR-605-3p inhibition. YY1 knockout inhibited migration (53–75%, p < 0.001), invasion (53–62%, p < 0.001), colony formation (43–53%, p < 0.001), and angiogenesis (p < 0.01). In U251 xenograft models, YY1 knockout reduced tumor volume from 2036 to 260 mm³ (p < 0.0001), partially restored to 1558 mm³ (p < 0.0001) by miR-605-3p antagomir, while agomir reduced it to 721 mm³ (p < 0.01). YY1 promoted angiogenesis, oxidative stress, inflammation, and fibrosis (p < 0.05), countered by miR-605-3p (p < 0.05). Validations included RT-qPCR, ChIP-qPCR, immunofluorescence, dual-luciferase assays, and immunohistochemistry. The YY1/BLACAT1/miR-605-3p axis drives GBM progression, offering therapeutic potential.